Language Styles of Advertisements In High End Magazine - Hariratul Jannah; Sumirna Sumirna; Nurhikmawati Nurhikmawati (Tamaddun Life, 2016)
The objectives of the research are to know how the language styles are used in advertisements High-End magazine and to know the kinds of language styles used in advertisements High-End magazine. This method of writing is descriptive by exposing aspects of language style contained in High-End magazine. In this study, the data obtained from High-End magazine, published in January 2014. The samples taken are 20 types of ads. In conclusion, there are eight kinds of language styles used by advertisers in High-End magazine. The language styles are the parable, metaphor, personification, prolepsis or anticipation, oxymoron, alliteration, asyndeton, and assonance.